STRATEGI JEPANG DALAM MEMILIKI KEPULAUAN SENKAKU 2012-2013 - Furqon, Muhammad; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is motivated by a dispute between Japan and China inhaving the Senkaku Islands. This study aims to describe the Senkaku Islands, anddescribe and explain the steps in the case of possession Japan the SenkakuIslands.This study used qualitative methods, the research done by way ofexplaining the way of outlining the problem based on the existing evidence. Thetechnique used to obtain secondary data and facts in order to study the problemin this paper is to use the research literature (library research) in the form ofbooks, literature, dictionaries, articles in magazines, scientific journals, bulletins,etc., and also documentation that can be accessed via the internet. Results revealthat the Senkaku Islands are 5 rocky uninhabited islands, but around the manyislands contained reserves of oil and natural gas.The steps that have been performed in Japan have Senkaku Islands are:(1) states and incorporate the Senkaku Islands as Japanese territory, (2) buy theSenkaku Islands from the Japanese private sector, (3) conduct a cordon near itsterritory from China, and conduct war games with the United States in the regionnear the Senkaku Islands, (4) joint consensus (joint Agreement) to administer theislands jointly.Keywords : Japanese Strategy, Senkaku Islands